A REVIEW OF HOMOLOBINAE (HYMENOPTERA: BRACONIDAE) OF SERBIA AND MONTENEGRO (Acta Entomologica Serbica, 2019)
This work presents the first retrospective of Homolobus species registered in Serbia and Montenegro. The following species are recorded: H. (Phylacter) annulicornis, H. (Homolobus) discolor, H. (Chartolobus) infumator and H. (Apatia) truncator.